Prediction of minimal encephalopathy in patients with HCV-related cirrhosis using albumin-bilirubin, platelets-albumin-bilirubin score, albumin-bilirubin-platelets grade and ammonia level - Ayman Alsebaey (Egyptian Liver Journal, 2020)
Abstract Background Minimal hepatic encephalopathy (MHE) is a complication of liver cirrhosis causing low quality of life, driving skills and higher traffic violation. The neuro-psychometric tests are the gold standard but difficult clinically and time-consuming. The aim was to assess albumin-bilirubin (ALBI), platelets-albumin-bilirubin (PALBI) score, albumin-bilirubin-platelets (ALBI-PLT) grade and ammonia level as MHE predictors. All the patients (n = 257) underwent critical flicker frequency number connection, serial dotting and digit symbol test for MHE diagnosis (n = 166, 64.6%). Liver function, INR, CBC and arterial ammonia were measured. Results There was statistically significant difference (p < 0.05) between MHE patients and those without as regards ammonia (86.59 ± 23.25 vs. 63.56 ± 24.2 μmol/L), ALBI score (−2.13 ± 0.53 vs. −2.49 ± 0.38), PALBI score (−2.33 ± 0.39 vs. −2.55 ± 0.26) and ALBI-PLT (3.98 ± 0.49 vs. 3.70 ± 0.56). Patients with MHE were mainly Child-Pugh B and C and also ALBI grade 2 and 3. For MHE discrimination, ALBI, PALBI, ALBI-PLT and ammonia had the following cutoffs >−2.36 (57.23% sensitivity, 77.78% specificity), >−2.5 (60.84% sensitivity, 67.9% specificity), > 3 (87.35% sensitivity, 27.16% specificity) and > 76.5 (69% sensitivity, 72.5% specificity) respectively (p = 0.001). On comparison of the area under the curve, ALBI is comparable to PALBI (p = 0.245) and ammonia (p = 0.603). The ALBI-PLT is inferior to ALBI (p = 0.018) and ammonia (p = 0.021) but comparable to PALBI (p = 0.281). ALBI (odds = 5.64), PALBI (odds = 7.86), ALBI-PLT (odds = 2.86), ammonia (odds = 1.05), Child-Pugh score (odds = 2.13), MELD (odds = 1.26) are independent predictors of MHE. Conclusion ALBI, PALBI and ammonia are clinical useful model for MHE prediction.